Decrease in p3‐Alcβ37 and p3‐Alcβ40, products of Alcadein β generated by γ‐secretase cleavages, in aged monkeys and patients with Alzheimer's disease - Saori Hata; Chiori Omori; Ayano Kimura; Haruka Saito; Nobuyuki Kimura; Veer Gupta; Steve Pedrini; Eugene Hone; Pratishtha Chatterjee; Kevin Taddei; Kensaku Kasuga; Takeshi Ikeuchi; et al. (Alzheimer’s & Dementia: Translational Research & Clinical Interventions)
Abstract Introduction Neuronal p3‐Alcβ peptides are generated from the precursor protein Alcadein β (Alcβ) through cleavage by α‐ and γ‐secretases of the amyloid β (Aβ) protein precursor (APP). To reveal whether p3‐Alcβ is involved in Alzheimer's disease (AD) contributes for the development of novel therapy and/or drug targets. Methods We developed new sandwich enzyme‐linked immunosorbent assay (sELISA) systems to quantitate levels of p3‐Alcβ in the cerebrospinal fluid (CSF). Results In monkeys, CSF p3‐Alcβ decreases with age, and the aging is also accompanied by decreased brain expression of Alcβ. In humans, CSF p3‐Alcβ levels decrease to a greater extent in those with AD than in age‐matched controls. Subjects carrying presenilin gene mutations show a significantly lower CSF p3‐Alcβ level. A cell study with an inverse modulator of γ‐secretase remarkably reduces the generation of p3‐Alcβ37 while increasing the production of Aβ42. Discussion Aging decreases the generation of p3‐Alcβ, and further significant decrease of p3‐Alcβ caused by aberrant γ‐secretase activity may accelerate pathogenesis in AD.